2023
DOI: 10.1007/s00500-023-08236-3
|View full text |Cite
|
Sign up to set email alerts
|

A numerical framework for modeling the dynamics of micro-organism movement on Carreau-Yasuda layer

Abstract: Gliding motility often noticed in phylogenetically rod-shaped bacteria which locomote via dissipating their own energy. The said gliding motion via producing waves and secreting slime is generally witnessed in gram-negative bacteria. The influence of Inertia in slime layer beneath glider is also a significant feature to this mechanism. The propulsive microbe pushes the slime backwards, while reactive forces in the slime aids a forward movement of the propeller. Out of several motility modes the complex wavy gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The widely utilized Homotopy method (OHAM) is applied to obtain the solution, and it is determined that the Casson fluid and normalized slip both increase entropy generation. Some interesting studies related to non‐Newtonian fluids [18–23], Graetz problem [24–38] gliding bacteria [39–42] and robust numerical approaches [43–45] are worthwhile to mention. Motivated by above mention studies, we aim to elaborate on the impact of axial conduction and viscous dissipation on the Graetz problem inside the tube using Casson viscoplastic fluid under imposed heat flux at the wall.…”
Section: Introductionmentioning
confidence: 99%
“…The widely utilized Homotopy method (OHAM) is applied to obtain the solution, and it is determined that the Casson fluid and normalized slip both increase entropy generation. Some interesting studies related to non‐Newtonian fluids [18–23], Graetz problem [24–38] gliding bacteria [39–42] and robust numerical approaches [43–45] are worthwhile to mention. Motivated by above mention studies, we aim to elaborate on the impact of axial conduction and viscous dissipation on the Graetz problem inside the tube using Casson viscoplastic fluid under imposed heat flux at the wall.…”
Section: Introductionmentioning
confidence: 99%
“…They numerically deployed their models using the Adomian decomposition method. Das et al [25], Kada et al [26] and Asgar et al [27] demonstrated the MHD movement of a three-dimensional Carreau-nanofluid under the effect of different physical situations. The results of this experiment demonstrate that the heat generating parameter raised the nanofluid's temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Motion resistance is an essential fluid characteristic, and its mechanism analysis, simulation, and regulation are widely studied [5][6][7][8][9][10][11]. The method of coating the flow surface with drag-reduction materials to reduce the roughness and enhance protective capabilities was first applied to long-distance oil and gas pipelines, such as the Zeepipe pipeline in Norway [12] and the Alliance pipeline between Canada and the United States [13], both of which were internally coated with epoxy resin.…”
Section: Introductionmentioning
confidence: 99%